A revision of the South African endemic water beetle genus Pneuminion Perkins (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2004)
The South African endemic water beetle genus Pneuminion Perkins, 1997 is revised. The generic limits, habitat preferences and morphological characters are discussed. A key to the nine known species is given. New species described are P. balfourbrownei, P. endroedyi, P. impressum, P. nanum, P. natalensis, P. punctatum, P. semisulcatum, and P. tubum. High resolution digital images of the holotypes are presented (online version in color), the male genitalia are illustrated, and the geographical distributions are mapped.